The impact of foreign direct investment on financial performance An analytical study of the data of a sample of foreign companies operating in the oil and gas sector In the Kurdistan Region of Iraq for the period from 2009-2018 - Ahmad Mohammed, Shivan; Mohammed Abdulrahman, Ibrahim (Academic Journal of Nawroz University, 2022)
This study seeks to achieve the impact of foreign direct investment on the financial performance of multinational companies during the study period, and a set of financial ratios were applied to analyze the historical data of foreign companies in the study sample for the period from (2009-2018), in addition to applying a number of statistical methods to analyze the relationship between study variables. The study reached a set of conclusions, the most important of which is that most of the companies’ investments in the study sample are concentrated in the branch of the Kurdistan Region of Iraq, and this is the interest of these foreign companies in the economy of the region, and this is an indication of the extent to which the main companies depend on the branch of the region, and it was found from the financial analysis of the study that the branch of the region It has a significant impact on the company's main performance. Based on the findings of the study, A set of proposals was presented, including the study of several different alternatives in order to choose the best alternative and benefit more from the investment.